2012
DOI: 10.1007/s10549-012-2289-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of epidermal growth factor receptor in breast cancer

Abstract: Decades of research in molecular oncology have brought about promising new therapies that are designed to target specific molecules that promote tumor growth and survival. The epidermal growth factor receptor (EGFR) is one of the first identified important targets of these novel antitumor agents. Approximately half of cases of triple-negative breast cancer (TNBC) and inflammatory breast cancer (IBC) overexpress EGFR. Thus, EGFR inhibitors for treatment of breast cancer have been evaluated in several studies. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
485
2
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 623 publications
(513 citation statements)
references
References 83 publications
15
485
2
11
Order By: Relevance
“…Although HER2 is classically considered upstream of PI3K, these results indicate that under certain conditions, interactions between mutant PIK3CA and mutant HER2 may lead to "rewiring" and dysregulation of signaling pathways. Similar pathway dysregulation has been reported in other studies (17,21,22). Because PIK3CA mutations have been shown to confer EGFindependent growth properties to MCF-10A cells, we tested if HER2 mutations could augment this phenotype.…”
Section: Acinar Morphology and Anchorage Independent Growth In Mcf7supporting
confidence: 74%
“…Although HER2 is classically considered upstream of PI3K, these results indicate that under certain conditions, interactions between mutant PIK3CA and mutant HER2 may lead to "rewiring" and dysregulation of signaling pathways. Similar pathway dysregulation has been reported in other studies (17,21,22). Because PIK3CA mutations have been shown to confer EGFindependent growth properties to MCF-10A cells, we tested if HER2 mutations could augment this phenotype.…”
Section: Acinar Morphology and Anchorage Independent Growth In Mcf7supporting
confidence: 74%
“…Previous studies have revealed a role for the ERK/MAPK pathway in the evasion of anoikis. 21,24,27,32 In order to assess the activation of ERK signaling in IBC cells, we examined phospho-ERK levels in KPL-4 cells deficient in ErbB2 or SUM149 cells deficient in EGFR. In each case, we discovered that the deficiency in receptor tyrosine kinase expression (i.e., ErbB2 in KPL-4 and EGFR in SUM149) resulted in a concomitant loss of phospho-ERK (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…17 It has become clear that tumor progression and metastasis require cancer cells to inhibit anoikis, oftentimes through alterations in intracellular signaling pathways. [18][19][20] Interestingly, previous studies have shown that ErbB2 and EGFR, which are hyperactivated in a substantial percentage of IBC patients, 21 can effectively antagonize the anoikis program to facilitate anchorage-independent growth. [22][23][24][25][26][27][28] However, a detailed examination of the molecular mechanisms underlying anoikis inhibition in IBC cells has yet to be completed.…”
mentioning
confidence: 99%
“…It was suggested that EGFR activation drives migration and invasion of tumor cells through epithelial-mesenchymal transition and alters chemosensitivity by rewiring the apoptotic signaling network. 35 However, the utility of high EGFR copy number as a predictive biomarker for EGFR-targeted therapy and as a prognostic factor for triple-negative breast cancer should be validated in large studies.…”
Section: Discussionmentioning
confidence: 99%